2022
DOI: 10.1093/plphys/kiac558
|View full text |Cite
|
Sign up to set email alerts
|

Sophora moorcroftiana genome analysis suggests association between sucrose metabolism and drought adaptation

Abstract: Expansion of sucrose pathway genes may contribute to the extensive root system and drought resistance of S. moorcroftiana.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Multiomics analysis revealed that the 2-oxocarboxylate metabolism and isoflavone biosynthesis pathways were the core pathways involved in mepiquine-mediated regulation of the drought response in soybean, and candidate genes involved in these processes were also identified (Wang et al, 2023b). WGCNA combined with metabolomic and transcriptomic analyses has indicated that the sucrose metabolism pathway genes AMY3 and CWINV1 are responsible for the relatively high sucrose content in the roots of Schisandra chinensis, which in turn promoted the development of the root system and increased drought resistance (Yin et al, 2023). In another study, the transcriptome and metabolome of Cyclocarya paliurus under different PEG concentrations were analyzed, and WGCNA revealed that 3 key modules, 8 structural genes and 14 regulatory transcription factors regulate sugar metabolism under drought stress (Li et al, 2023a).…”
Section: Introductionmentioning
confidence: 99%
“…Multiomics analysis revealed that the 2-oxocarboxylate metabolism and isoflavone biosynthesis pathways were the core pathways involved in mepiquine-mediated regulation of the drought response in soybean, and candidate genes involved in these processes were also identified (Wang et al, 2023b). WGCNA combined with metabolomic and transcriptomic analyses has indicated that the sucrose metabolism pathway genes AMY3 and CWINV1 are responsible for the relatively high sucrose content in the roots of Schisandra chinensis, which in turn promoted the development of the root system and increased drought resistance (Yin et al, 2023). In another study, the transcriptome and metabolome of Cyclocarya paliurus under different PEG concentrations were analyzed, and WGCNA revealed that 3 key modules, 8 structural genes and 14 regulatory transcription factors regulate sugar metabolism under drought stress (Li et al, 2023a).…”
Section: Introductionmentioning
confidence: 99%